Hidden figures the American Dream and the untold story of the black women mathematicians who helped win the space race - Shetterly, Margot Lee 1969- (William Morrow, an imprint of HarperCollins Publishers, 2017)
"Before John Glenn orbited the earth or Neil Armstrong walked on the moon, a group of dedicated female mathematicians known as "human computers" used pencils, slide rules, and adding machines to calculate the numbers that would launch rockets, and astronauts, into space. Amonge these problem-solvers were a group of exceptionally talented African American women. Originally math teachers in the South's segregated public schools, these gifted professionals answered Uncle Sam's call during the labor shortages of World War II. With new jobs at the fascinating, high-energy world of the Langley Memorial Aeronautical Laboratory in Hampton, Virginia, they finally had a shot at jobs that would push their skills to the limits. Even as Virginia's Jim Crow laws required them to be segregated from their white counterparts, the women of Langley's all-black "West Computing" group helped America achieve one of the things it desired most: a decisive victory over the Soviet Union in the Cold War, and complete domination of the heavens. Starting in WW II and moving through to the Cold War, the Civil Rights Movement, and the Space Race, Hidden Figures follows the interwoven accounts of Dorothy Vaughan, Mary Jackson, Katherine Johnson, and Christine Darden - four African American women who participated in some of NASA's greatest successes. It chronicles their careers over nearly three decades as they faced challenges, forged alliances, and used their intellect to change their own lives, and their country's future." Buchrückseite
Enthält am Ende 14 Seiten mit zusätzlichen Informationen (Interview, Reading Group Guide)
Keywords: Schwarze; Mathematikerin; Raumfahrtprogramm; Geschichte; USA; Biografie